2015
DOI: 10.20472/te.2015.3.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Reading performance, learning strategies, gender and school language as related issues – PISA 2009 findings in Finland and Estonia

Abstract: Abstract:Reading is considered an important skill not only for academic success, but also for active participation in society. International student literacy assessments report gender

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Despite the fact that the PISA instrument has been widely used in research (Mak et al, 2017;Säälik, 2015), there is a lack of empirical evidence on the cross-cultural comparability and criterion validity of the PISA 2009 metacognition scenarios. Two empirical studies reported on the measure of metacognitive knowledge scored based on the pair-wise comparison method.…”
Section: Metacognitive Knowledge In Reading In Pisa 2009mentioning
confidence: 99%
“…Despite the fact that the PISA instrument has been widely used in research (Mak et al, 2017;Säälik, 2015), there is a lack of empirical evidence on the cross-cultural comparability and criterion validity of the PISA 2009 metacognition scenarios. Two empirical studies reported on the measure of metacognitive knowledge scored based on the pair-wise comparison method.…”
Section: Metacognitive Knowledge In Reading In Pisa 2009mentioning
confidence: 99%
“…Brozo et al (2013) emphasize the importance of cooperation between teachers from different disciplines and literacy experts in teaching reading strategies and creating related classroom activities. Since teachers and schools have an opportunity to help their students by teaching those skills, their awareness of useful strategies may possibly depend on teaching at school (Säälik, 2015). In this context, policy makers and teachers have important roles in teaching and development of metacognitive skills.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…These levels were coded with values from 1 to 4. Following previous work (Ehmke & Siegle, 2005; Säälik, 2015), only the highest level from both parents was used in the analyses.…”
Section: Methodsmentioning
confidence: 99%